THE Pengaruh Risiko Kredit Dan Risiko Operasional Terhadap Kinerja Perbankan Pada Bank BUMN Yang terdaftar di BEI Periode 2012-2020 - Edah Komalasari; Gusganda Suria Manda (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose behind this review was to decide if the reliant variable in this review could be affected by the autonomous variable. The populace in this review were 4 Persero Business Saves money with the examining procedure utilized was purposive testing. Gotten an example of 4 state-claimed business banks enlisted with the OJK. In this review, different relapse was utilized to test the speculation. In view of the aftereffects of concurrent testing, it is realized that ROA can be impacted by NPL and BOPO together. In light of the fractional test, ROA can't be impacted by NPL and ROA can be impacted by BOPO..